2023
DOI: 10.3390/earth4030038
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensitivity of Penman–Monteith Reference Evapotranspiration to Climatic Variables in Mato Grosso, Brazil

Marlus Sabino,
Adilson Pacheco de Souza

Abstract: Understanding how climatic variables impact the reference evapotranspiration (ETo) is essential for water resource management, especially considering potential fluctuations due to climate change. Therefore, we used the Sobol’ method to analyze the spatiotemporal variations of Penman–Monteith ETo sensitivity to the climatic variables: downward solar radiation, relative humidity, maximum and minimum air temperature, and wind speed. The Sobol’ indices variances were estimated by Monte Carlo integration, with samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In Table 4, the parameters required for ETo estimates are denoted by " ▀▀ ", while "X" denotes that they were not employed in the corresponding method. Sabino and Souza [78] indicated that changes in solar radiation, relative humidity, and wind speed are the main driving forces that impact the ETo. In addition, RHmean and Ws have higher sensitivity indices during the dry season, which is also affirmed in our study area as it is arid in nature.…”
Section: Study Discussionmentioning
confidence: 99%
“…In Table 4, the parameters required for ETo estimates are denoted by " ▀▀ ", while "X" denotes that they were not employed in the corresponding method. Sabino and Souza [78] indicated that changes in solar radiation, relative humidity, and wind speed are the main driving forces that impact the ETo. In addition, RHmean and Ws have higher sensitivity indices during the dry season, which is also affirmed in our study area as it is arid in nature.…”
Section: Study Discussionmentioning
confidence: 99%
“…The increase in ETo from 2050 onwards in RCP 4.5 and 8.5 projections is, in general, justified due to the gradual and continuous increase in air temperature values since the RCP 2.6 scenario presents temperature stabilization and consequent stagnation of ETo averages in the mid-21st century (Figure 4) [36,39]. However, changes in other meteorological variables have important contributions to changes in evapotranspiration since ETo estimates using the PM method in the state are more sensitive to changes in RH and WS than to temperature [40]. Thus, the distinction between the ETo averages estimated in RCPs 4.5 and 8.5 is mainly due to the reduction in relative humidity and increase in wind speed (Figure 4), which occur more significantly in RCPs 8.5, enabling the scenario pessimism to become statically different from the current conditions observed already between the years 2050-2075 (Table 2).…”
Section: Eto (Mm Daymentioning
confidence: 98%
“…In general, the two models with the best results for estimating ETo in Mato Grosso in the current period (2007-2020) were CESM1-CAM5 and HadGEM2-ES. However, since the HadGEM2-ES model presented less dispersion of ETo estimation errors, as well as better performance in estimating the variables SRD, RH and SW, these variables have a greater impact on ETo estimates using the method of Penman-Monteith for the region [40]; in the following stages of this research, the MCG HadGEM2-ES will be the model used in the evaluations of ETo projections.…”
Section: Choice Of Climate Projection Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained by Yong et al [23] indicated that the global sensitivity analysis studies are recent and restricted to a few countries (Australia, Malaysia, the United States, and China). A recent work by Sabino and de Souza [24] presented a study of global sensitivity analysis for the Penman-Monteith model to calculate the reference evapotranspiration in the state of Mato Grosso, Brazil, using the Sobol' method.…”
Section: Previous Studiesmentioning
confidence: 99%